Evaluation of the Effect of Aerial Parts of Scrophularia atropatana Grossh Total Extracts on Analgesic Activity and Morphine Induced Tolerance in Mice - Bohloul Habibi asl; Zahra Majidi; Kiarash Fekri; Abbas Delazar; Haleh Vaez (Tabriz University of Medical Sciences, 2018)
Background: Scrophularia atropatana contains chemicals activating the GABA system and inhibiting glutaminergic system. As well as we know, drugs inhibiting glutamate system have analgesic effects and reduce tolerance to the analgesic effects of morphine. In the present study, effect of methanol extract of aerial parts of S. atropatana on tolerance to the analgesic effects of morphine was evaluated. Methods: The aerial parts of S. atropatana were extracted with methanol by maceration and was further analyzed to determine the content of total phenols, antioxidant activity (DPPH method) and analgesic activity. Several groups of mice received drug regimens for 4 days. Group I: Saline (10 ml/kg, i.p.) + Saline (10 ml/kg, i.p.), group II: Morphine (50mg/kg, i.p.) + Saline (10mg/kg, i.p.) and group III: Morphine (50mg/kg, i.p.) + Extract of S. atropatana (100, 200, 400 mg/kg, i.p.)]. On the fifth day the test dose of morphine (9 mg/kg, i.p.) in different groups were assessed. By using hot plate test, the analgesic activity of different doses of the extract was evaluated. Results: Phytochemical screening indicated the presence of total phenolics content of the extract (152 mg GAE/g) and antioxidant activity (RC50 =143µg/ml) in DPPH method. All doses of the extract had analgesic activity. It was found that treatment with extract (100, 200 mg/kg, i.p.) attenuated the development of tolerance to the antinociceptive effect of morphine. Conclusion: The results of the study demonstrate that S. atropatana strongly reduced tolerance to morphine and has analgesic effects. The suggested analgesic effects may be related to the phenolics content and antioxidant activity of the plant alongside inhibition of glutaminergic system.